KEANEKARAGAMAN DIPTERA (INSECTA) DI GUNUNG KENDENG DAN GUNUNG BOTOL, TAMAN NASIONAL GUNUNG HALIMUN, JAWA BARAT - Tri Atmowidi; Taruni Sri Prawasti; Sugeng Utomo; Yana Kurniawan (BERITA BIOLOGI, 2001)
Diptera is one of the four largest orders of insects (the three others are Coleoptera, Lepidoptera and Hymenoptera).Presently, about 108 families of Diptera were recoqnized and over 150.000 species have been described worldwide.This study was conducted to explore the diversity of Diptera in Gunung Halimun National Park, West Java.Sampling of Diptera has been conducted in Mt. Kendeng (1.200 - 1.300 m asl) and mount Botol (1.650 and 1.750 m asl) using yellow pan traps, Malaise traps, light traps, and sweep nets. The diversity of Diptera were analyzed using Shannon's diversity index and evenness, and Jaccard's similarity index (Magurran 1987). In this study, we found 49 families of Diptera (12 families are Nematocera and 37 families are Brachycera). The diversity of Diptera in Mt. Kendeng was higher (Shannon diversity index; H' =2.92) than that in Mt. Botol (H' = 2.46). The similarity of Diptera in Mt. Kendeng and Mt. Botol was 60%(Jaccard's similarity index; Cj=0.6).